OPTIMALISASI PEMASARAN DIGITAL PADA UMKM CEMAL CEMIL CEMILANKU - Yuliafitri, Indri; Arum Kanti, Runita (LPPM Univ. Ibn Khaldun Bogor, 2022)
During the Covid-19 pandemi, Micro, Small, and Medium Enterprises (MSMEs) must be creative in marketing. The pandemi has changed people's behavior in transactions, from conventional transactions to online transactions. So that the marketing media has changed by using digital media. The first step to doing digital marketing is to make attractive product packaging, then make product photos as marketing media which will later be displayed in digital marketing media. Cemal Cemil Cemilanku is an MSME that sells snacks made from dumpling skin. The packaging and marketing carried out by MSMEs are still simple. So that these MSMEs can expand their market share, training and assistance in managing Instagram social media and shopee online stores are carried out. The results of this training and mentoring show an increase in sales of MSMEs obtained online.